2005
DOI: 10.1590/s0004-28032005000400012
|View full text |Cite
|
Sign up to set email alerts
|

Trimethoprim-sulfamethoxazole versus norfloxacin in the prophylaxis of spontaneous bacterial peritonitis in cirrhosis

Abstract: -Background -The prognosis of patients with chronic liver disease and spontaneous bacterial peritonitis is poor, being of great importance its prevention. Aim -To compare the effectiveness of trimethoprim-sulfamethoxazole versus norfloxacin for prevention of spontaneous bacterial peritonitis in patients with cirrhosis and ascites. Patients and Methods -Fifty seven patients with cirrhosis and ascites were evaluated between March 1999 and March 2001. All of them had a previous episode of spontaneous bacterial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
2
37
0
2
Order By: Relevance
“…Nearly a quarter of our cohort died during the study period, with no difference in mortality rate between the N and T‐S groups, similar to other studies using SBP prophylaxis . While we found that the survival rate free of transplantation at 12 months was lower in patients who had an infection than in those who did not, this was not significant (32.5% vs 47.5%, P = 0.18).…”
Section: Discussionsupporting
confidence: 87%
“…Nearly a quarter of our cohort died during the study period, with no difference in mortality rate between the N and T‐S groups, similar to other studies using SBP prophylaxis . While we found that the survival rate free of transplantation at 12 months was lower in patients who had an infection than in those who did not, this was not significant (32.5% vs 47.5%, P = 0.18).…”
Section: Discussionsupporting
confidence: 87%
“…However, four trials also included patients with prior SBP132 139 142 143 and the remaining have recently been summarised in two meta-analyses 136 137. Surprisingly, these came to different conclusions, most likely due to erroneous data extraction 144.…”
Section: Prevention Of Sbpmentioning
confidence: 99%
“…Several independent studies and meta-analysis have assessed this issue [68][69][70][71] . In a placebo-controlled trial on patients with protein ascitic levels < 15 g/L and advanced liver failure or impaired renal function, norfloxacin (400 mg/d) reduced the 1-year probability of developing SBP and improved the 3-mo survival, although at 1 year the difference in survival was not significant [29] .…”
Section: Primary Prophylaxis In Patients With Ascitesmentioning
confidence: 99%